2018
DOI: 10.1590/0102-4698189927
|View full text |Cite
|
Sign up to set email alerts
|

Connecting, swiping, and integrating: mobile apps affordances and innovation adoption in teacher education and practice

Abstract: Despite society’s adoption of mobile devices, we have yet to learn whether teachers perceive these artifacts as an innovation and what their potential is for teacher development and practice. This study aims to answer the following questions: what does mobile application affordances teachers perceive for their professional development and practice? What do these affordances reveal concerning Rogers (2003) innovation attributes, namely: relative advantage, compatibility, complexity, trialability, and observabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The attitudes toward adopting innovations have an influence on forming digital literacy (Cirus & Simonova, 2021). Additionally, the characteristics of adopting innovation help to facilitate and support the digital literacy of students (Gunter, 2018). Overall digital literacy is increased through the diffusion of innovation (Matyunina, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The attitudes toward adopting innovations have an influence on forming digital literacy (Cirus & Simonova, 2021). Additionally, the characteristics of adopting innovation help to facilitate and support the digital literacy of students (Gunter, 2018). Overall digital literacy is increased through the diffusion of innovation (Matyunina, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, negative emotions towards employing social media can affect all areas of life, including work, and influence teacher burnout. Gunter and Braga (2018) decided to shut down traditional teaching practices so focused on teachers using technology, especially online mobile devices via Apps, to develop the oral skills of the teachers which led to a decrease in their sense of burnout. Besides, Çelik et al (2018) examined the importance of Mobile affordance and showed that mobile technologies offer new affordances for teacher observation in teacher education programs, making them more motivated.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the gathered results, the most recurrent affordances refer to the use of audio materials produced during the interactions via WhatsApp to develop the oral skills of the teachers themselves. While reflecting on pedagogical affordances for improving their students' oral skills, the teachers used voice recording functionalities during the course to improve their pronunciation based on their peers' productions, to develop their oral comprehension in English, to use authentic language, to mention a few affordances (as cited in Gunter & Braga, 2018).…”
Section: Teachers Mobile Affordancesmentioning
confidence: 99%
See 2 more Smart Citations